2022
DOI: 10.17305/bjbms.2022.7416
|View full text |Cite
|
Sign up to set email alerts
|

PLCE1 is a poor prognostic marker and may promote immune escape from osteosarcoma by the CD70-CD27 signaling pathway

Abstract: Phospholipase C epsilon 1 (PLCE1) is involved in the pathogenesis of many cancers. However, the biological role of PLCE1 in osteosarcoma (OS) is still poorly understood. The prognostic survival analysis was performed on the PLCE1gene in the TARGET data set and the differential expression of PLCE1 in OS tissue and normal bone tissue on the tissue chip was detected by immunohistochemistry. Spearman’s rank correlation coefficient analysis was implemented to explore the relationship between PLCE1 and immune genes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 51 publications
(76 reference statements)
1
1
0
Order By: Relevance
“…As the effector of heterotrimer and small G protein, PLCE1 is involved in regulating cell growth, T-cell activation, actin organization and cell survival. The GWAS results of the mapping to the PLCE1 gene function were mostly related to nervous system activity, which regulates the function of the brain in different ways, and the brain was key to regulating diet behavior and body energy homeostasis [36][37][38][39]. We showed that the candidate genes identified were key and might affect the feed efficiency of Wenchang chickens, and the gene expression level in the high and low RFI groups of broilers also validated this result.…”
Section: Feed Efficiency Traits Genome-wide Association Studiessupporting
confidence: 60%
“…As the effector of heterotrimer and small G protein, PLCE1 is involved in regulating cell growth, T-cell activation, actin organization and cell survival. The GWAS results of the mapping to the PLCE1 gene function were mostly related to nervous system activity, which regulates the function of the brain in different ways, and the brain was key to regulating diet behavior and body energy homeostasis [36][37][38][39]. We showed that the candidate genes identified were key and might affect the feed efficiency of Wenchang chickens, and the gene expression level in the high and low RFI groups of broilers also validated this result.…”
Section: Feed Efficiency Traits Genome-wide Association Studiessupporting
confidence: 60%
“…As a multistage and multifactorial process, CRC metastasis remains a major cause of high mortality and poor prognosis. Recent studies have reported that abnormal lipid metabolism is involved in the progression of CRC, and many genes related to lipid metabolism have been found to play an oncogenic role [2][3][4][5][6]. Apolipoprotein E (apoE) is a secreted protein involved in lipid metabolism and in the development of Alzheimer's disease and atherosclerosis [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…As the effector of heterotrimer and small G protein, PLCE1 is involved in regulating cell growth, T-cell activation, actin organization and cell survival. Mapping the PLCE1 gene function were mostly related to nervous system activity, which regulates the function of the brain in different ways, and the brain was key to regulating diet behavior and body energy homeostasis [ 43 46 ].…”
Section: Discussionmentioning
confidence: 99%